Determining patient treatment preferences for management of acute pain episodes in irritable bowel syndrome. Issue 12 (2nd April 2021) - Almario, Christopher V.; Eberlein, Samuel; Khalil, Carine; Spiegel, Brennan M. R.
Abstract: Background: Many patients with irritable bowel syndrome (IBS) experience acute and unexpected pain episodes over and above chronic background symptoms, and there are emerging medications designed to treat such pain. We aimed to use conjoint analysis—a technique that elucidates how people make complex decisions—to examine patient preferences for emerging medicines for breakthrough IBS pain. Methods: We conducted a cross‐sectional conjoint analysis survey among patients with Rome IV IBS and recurrent episodes of acute pain to assess the relative importance of medication attributes in their decision‐making. We also assessed what respondents would require of subcutaneous (SQ) therapies to consider their use. Key Results: Among 629 patients with Rome IV IBS, 606 (96.3%) reported ≥1 acute pain episodes in the past month. For the 461 participants with multiple attacks who completed the conjoint analysis, they prioritized medication efficacy (importance score 34.9%), avoidance of nausea (24.3%), and avoidance of constipation (12.2%) as most important in their decision‐making. These were followed by route of administration (10.3%), avoidance of headache (9.3%), and avoidance of drowsiness (8.9%). Moreover, 431 (93.5%) participants would consider SQ therapies for their acute pain; they had varying expectations on the minimum pain decrease and onset and duration of pain relief needed for considering their use. Conclusions and Inferences: The vast majority of patients with IBS experience breakthrough pain, and when selecting among therapies, they prioritize efficacy and most are willing to use a rapid‐acting SQ treatment. These results support development of novel, effective medications—oral or SQ—for management of acute pain attacks. Abstract : Using conjoint analysis, we found that IBS patients prioritize medicine efficacy and avoidance of nausea when choosing a therapy for acute pain, and most are open to using a SQ treatment. These result support development of novel medicines—oral or SQ—for treating pain attacks.